Informal Caregivers of Cancer Patients: Review of Interventions, Care Activities, and Outcomes. (July 2018) - Frambes, Dawn; Given, Barbara; Lehto, Rebecca; Sikorskii, Alla; Wyatt, Gwen
Family and friends are important resources for patients during cancer treatment and warrant an expanded review of not only what they contribute to patient care but also the support they need and the personal consequences of caregiving. A review of 14 randomized controlled trials published between 2009 and 2016 was completed utilizing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. The results of this review expand the scope of what is known regarding relationships among supportive interventions for caregivers, activities performed to care for cancer patients, caregiver characteristics, and health outcomes of caregivers. Specific results include (a) updated synthesis of literature associated with variables important to caregiving, (b) attention to interventions designed to support caregivers, (c) classification of specific activities caregivers perform for cancer patients, (d) identification of caregiver characteristics associated with specific care activities, (e) inconsistencies in measurement of care activities, and (f) minimal reporting of outcome variables.